Holocene demographic fluctuations, climate and erosion in the Mediterranean: A meta data-analysis. (May 2019) - Walsh, Kevin; Berger, Jean-François; Roberts, C Neil; Vanniere, Boris; Ghilardi, Matthieu; Brown, Antony G; Woodbridge, Jessie; Lespez, Laurent; Estrany, Joan; Glais, Arthur; Palmisano, Alessio; Finné, Martin; et al.
As part of the Changing the Face of the Mediterranean Project, we consider how human pressure and concomitant erosion has affected a range of Mediterranean landscapes between the Neolithic and, in some cases, the post-medieval period. Part of this assessment comprises an investigation of relationships among palaeodemographic data, evidence for vegetation change and some consideration of rapid climate change events. The erosion data include recent or hitherto unpublished work from the authors. Where possible, we consider summed probabilities of 14 C dates as well as the first published synthesis of all known optically stimulated luminescence dated sequences. The results suggest that while there were some periods when erosion took place contemporaneously across a number of regions, possibly induced by climate changes, more often than not, we see a complex and heterogeneous interplay of demographic and environmental changes that result in a mixed pattern of erosional activity across the Mediterranean.